Impulsivity and Parkinson’s disease: More than just disinhibition() - Antonelli, Francesca (2011)
In the last few years it has become clear that impulsivity is a complex behaviour composed of different domains and dependent on different neural networks. The proposed pathogenetic mechanisms for the emergence of impulsivity disorders in Parkinson’s Disease (PD) can be broadly separated into three potentially interacting processes: the contribution of premorbid susceptibility to impulsivity, the contribution of the disease itself to the behaviour and the potential contribution of therapeutic agents. Growing evidence suggests that dopamine and the subthalamic nucleus are playing a certain role in the pathophysiology of different aspects of impulsivity. In this review, we summarise the main concepts defining various components of impulsivity both in healthy subjects and patients affected by PD.